Satu Dekade Informasi Akuntansi dan Market Venture di Perusahaan Manufaktur Bursa Efek Indonesia - Risa Mardiana; Nurmala Ahmar; Syahril Djaddang (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2016)
A B S T R A C T The purpose of this study is prove empirically accounting information affects market venture. This study discusses the accounting information and market ventures in manufacturing companies 2005-2014 Indonesia stock exchange as measured by Degree of Operating Leverage, Degree of Financial Leverage, Degree of Total Leverage, and Earnings. This research is quantitative research with panel data regression with 9.0 eviews to 107 of Manufacturing Indonesia. The study states that the overall absence of influence degree of operating leverage, degree of financial leverage, degree of total leverage and earnings against market venture and the difference results in a year on the degree of operating leverage, degree of financial leverage, degree of total leverage and earnings of the venture market. Research can add a reference material and encourage research accounting on the capital markets, knowledge of information regarding the degree of operating leverage, degree of financial leverage, degree of total leverage and earnings for investment decisions in the capital market, information market venture to investors in a way build institutions and better recording venture market. A B S T R A K Tujuan penelitian ini adalah untuk membuktikan secara empiris tentang Accounting Information mempengaruhi Market Venture. Penelitian ini membahas mengenai informasi akuntansi dan market venture di perusahaan manufaktur bursa efek indonesia 2005-2014 yang diukur dengan Degree of Operating Leverage, Degree of Financial Leverage, Degree of Total Leverage, dan Earnings. Penelitian ini adalah penelitian kuantitatif dengan regresi data panel dengan eviews 9.0 terhadap 107 Perusahaan Manufaktur Indonesia. Hasil penelitian menyatakan bahwa secara keseluruhan tidak terjadinya pengaruh degree of operating leverage, degree of financial leverage, degree of total leverage dan earnings terhadap market venture dan terjadinya perbedaan hasil secara per tahun pada degree of operating leverage, degree of financial leverage, degree of total leverage dan earnings terhadap market venture. Penelitian dapat menambah bahan referensi dan mendorong dilakukannya penelitian-penelitian akuntansi pada pasar modal, pengetahuan informasi mengenai degree of operating leverage, degree of financial leverage, degree of total leverage dan earning bagi keputusan investasi di pasar modal, pemberi informasi market venture kepada investor dengan cara membangun instansi dan pencatatan market venture lebih baik. JEL Classification: O16, G32, M41